The Degree of Possession of Digital Culture Skills by Students of the Faculty of Education at Latakia University in Light of the Skills of the Twenty-First Century (Journal of Hama University, 2026)
The research aimed to identify the degree of possession of digital culture skills by students of the Faculty of Education at Lattakia University in light of the skills of the twenty-first century. The descriptive approach and questionnaire were used as a research tool applied to a sample of (315) male and female students. The results showed that the degree of possession of digital culture skills by students of the Faculty of Education at Lattakia University amounted to (3.3), with a relative weight of (66%), at an average level, where information culture skills came in first place with a high degree, followed by information and communication culture skills in second place with an mediate degree, followed by media culture skills, at an mediate degree. It also showed that there were differences in the degree of possession of digital culture skills by students of the Faculty of Education in light of the skills of the twenty-first century attributed to the variable of the academic year, in favor of the final year students, and there were no differences attributed to the variable of the academic specialization. Accordingly, the researcher presented several proposals, the most important of which are: The necessity of including digital culture skills within the programs for preparing student teachers in the College of Education, and proposing a model for digital culture skills in light of the skills required for student teachers and their needs for them, in addition to drawing attention to the necessity of allocating an educational platform linked to digital culture skills.
Keywords: Key words: Digital literacy skills, College of Education students, 21st century skills.